PENGARUH KEPEMIMPINAN DIGITAL DAN MOTIVASI KERJA TERHADAP KREATIVITAS GURU DI SMAN 1 PASAMAN BARAT - Lastrioza, Lastrioza; Pasaribu, Rahmawaty; Gistituati, Nurhizrah; Rusdinal, Rusdinal; Nellitawati, Nellitawati (STKIP Pesisir Selatan, 2025)
Schools are required to adapt to the dynamics of the digital era through the implementation of leadership that can direct, facilitate, and inspire educators to be able to utilize technology creatively and productively. This study aims to describe and analyze the influence of the principal's digital leadership and work motivation on teacher creativity at SMAN 1 Pasaman Barat. The research approach used was qualitative with in-depth interviews to comprehensively explore teachers' experiences, views, and interpretations regarding digital leadership practices and the motivational drives that influence their creativity in learning activities. Research informants were selected purposively, consisting of the principal and several teachers actively involved in the implementation of digital-based learning. The results of the study indicate that the principal's digital leadership plays a significant role in fostering teacher motivation and creativity. The principal functions not only as an administrative decision-maker but also as an agent of change capable of building a collaborative, open, and innovation-oriented digital work culture. The principal's support in the form of training, guidance, and providing space for creative freedom has been proven to increase teacher enthusiasm in developing technology-based learning. On the other hand, teacher work motivation emerged as a reinforcing factor that channels positive energy towards the birth of new ideas.